La figura del coautore nelle letterature testimoniali in Italia - Comberiati, Daniele; Van Camp, Bieke (Incontri. Rivista europea di studi italiani, 2018)
The figure of the co-author in testimonial literature in ItalyBetween ca. 1990-1995, literary texts written by migrants with a native Italian co-author (most often presented as an editor) constituted a new phenomenon in the national literary panorama. If the topic has already been dealt with in historical and theoretical studies on Italian migration literature (Gnisci 1997; Parati 2005), a more in-depth study on the relationship between the co-author and testimonial literature is still lacking. Focusing on the Italian literary context, the aim of our article is to investigate the first phase of migration literature in comparison with deportation and concentration camp testimonies that, not surprisingly, have emerged since 1995 (Baldini 2012; Gordon 2012), when the first migrant productions began to run out. The similarities between the two types of texts are in fact numerous: in both cases the ‘testimonial contract’ (Lejeune 1975), although presented in different forms, is managed by the editor/co-author and not by the witness; there is a substantial difference between the legitimacy of the ‘witness’ and that of the author. Finally, the sensitivity of the public is in part the same and was culturally formed after the ‘Riflusso nel privato’ (litt. Backflow in the private sphere) of the 1980s (Crainz 2003).